Being human in a global age of technology - Whelton, Beverly J. B. (Nursing philosophy, 2016)
This philosophical enquiry considers the impact of a global world view and technology on the meaning of being human. The global vision increases our awareness of the common bond between all humans, while technology tends to separate us from an understanding of ourselves as human persons. We review some advances in connecting as community within our world, and many examples of technological changes. This review is not exhaustive. The focus is to understand enough changes to think through the possibility of healthcare professionals becoming cyborgs, human-machine units that are subsequently neither human and nor machine. It is seen that human technology interfaces are a different way of interacting but do not change what it is to be human in our rational capacities of providing meaningful speech and freely chosen actions. In the highly technical environment of the ICU, expert nurses work in harmony with both the technical equipment and the patient. We used Heidegger to consider the nature of equipment, and Descartes to explore unique human capacities. Aristotle, Wallace, Sokolowski, and Clarke provide a summary of humanity as substantial and relational.